A praxis for ethical research and scientific conduct in Greenland - Holm, Lene; Grenoble, Lenore; Virginia, Ross (Études/Inuit/Studies, 2011)
The last 30 years have seen remarkable changes in the political and social structure of Greenland. In 1979 Home Rule was proclaimed, giving the territory some measure of autonomy from Denmark. Self-Government (Naalakkersuisut) was instituted in June 2009 after a referendum, giving Greenland control over all areas of governance except foreign affairs and defence, which remain under Danish control. At present neither the Self-Government authorities nor any research body in Greenland has formulated a comprehensive code of ethics or guidelines for ethical and responsible conduct of research. In this paper we discuss the hazards of this legal vacuum and propose possible opportunities for moving forward. We consider the development of such codes to be integral to the development of science policy by the Self-Government authorities and an important tool for scientific engagement with the international community at a time when Greenland is making important decisions about resource development and sustainability.